Generation and Characterisation of Mesenchymal Stem Cells Derived from Placenta and Adult Cardiac Tissue - Vellasamy, Shalini (2011)
Mesenchymal Stem Cells (MSC) are adherent fibroblastic cells that are able to selfrenew and can differentiate to give rise to mesodermal lineages. MSC are nonhaematopoietic cells for they do not give rise to blood cell lineages but they support the haematopoiesis development in foetal and adult body. In addition, MSC were found to exhibit immunomodulatory effect on immune cells and cancer cells. In line with this, MSC have emerged as novel-cell based therapy to treat inflammations, autoimmune diseases, tumour growths and degenerative disorders which are considered as permanent and incurable diseases. This has increased the demands for MSC and has initiated the necessity to find alternative sources of MSC for an immediate and cost effective treatment. To date, there are some studies conducted on placenta, but little information is available on their immunomodulatory effects. Therefore, a comparative study was designed to investigate MSC derived from placenta tissues including umbilical cord, placenta (chorion and decidua basalis) and placental membrane (amnion) using enzymatic-dissociation method under one experimental condition. Besides, MSC were also generated from human adult cardiac tissues which were previously considered as terminally differentiated, post-mitotic organs lacking self renewal and regeneration potential. These MSC were characterised for their mesenchymal properties by means of cell surface markers via flowcytometric analysis, embryonic stem cell markers via reverse transcriptase PCR, differentiation potential and their immunomodulatory effect through tritiated thymidine cell proliferation, transwell, apoptosis and cell cycle assays. Placenta derived MSC were further assed for the effect of basic fibroblastic growth factor bFGF on the morphology and cell cycle kinetics of MSC. Both placenta and cardiac tissue derived MSC expressed common mesenchymal cell surface markers, embryonic stem cells markers and were able to differentiate into mesodermal lineages (adipocytes, osteocytes and chondrocytes). Interestingly, cardiac MSC had shown a more predetermined commitment into cardiac lineages as compared to bone marrow derived MSC. Supplementation of bFGF had significantly altered the morphology of MSC into more defined fibroblastic shape, enhanced growth kinetics, shortened doubling time, induced active cell cycle progression, delayed senescence,skewed the cytokine secretion profile and abundantly produced VEGF as compared to the MSC cultures without bFGF supplementation. Further functional study had demonstrated that UC-MSC and PLC-MSC significantly exerted a dose dependent inhibition on mitogenic stimulated T cell proliferation mainly via cell-to-cell contact than soluble factors (p<0.05). This inhibition was due to the arrest of T cells in G0 phase of cell cycle and not induced by apoptosis. However, this inhibitory effect was not specific to T lymphocytes, but also seen on other lymphocytes such as B cells and NK cells. Differently from T cells, MSC significantly prevented the transition from G1 S phase of NK cells (p<0.05). In addition, we have also shown for the first time that cardiac derived MSC exert immunosuppressive effect on immune cells apart from their predetermined commitment into cardiac lineages. This study revealed that UC-MSC stands out to be a potential alternative source of MSC as they display mesenchymal properties and had significantly suppressed various immune cells as compared to PLC-MSC. Furthermore, we also show that cardiac MSC could be a potential therapeutic tool in regenerating and treating a diseased heart. Our findings are fundamental and provide a platform for future use of these MSC as a cell based therapy in controlling unwanted immune responses and organ regeneration.